Genomics research: Prospects for improving livestock productivity - Nene, Vishvanath M.; Morzaria, S.P.; Baker, L.; Odonyo, A.; Rege, J.E.O.; Zerbini, E.; Bishop, Richard P. (CGIAR System Organization, 2000)
In this paper genomic research is discussed with regard to prospects for improving livestock productivity. Topics of discussion include, constraints to livestock productivity in developing countries; biotechnology research at ILRI; improvement of rumen fermentation; livestock genetic resources and genetics of disease resistance; animal health improvement by vaccine Development; Developments in genomics research; relevance of T. parva genome sequence for ECF; partnership in sequencing T. parva; and constraints to delivery.